Herbicides as Weed Control Agents: State of the Art: II. Recent Achievements. Issue 3 (7th August 2014) - Kraehmer, Hansjoerg; van Almsick, Andreas; Beffa, Roland; Dietrich, Hansjoerg; Eckes, Peter; Hacker, Erwin; Hain, Ruediger; Strek, Harry John; Stuebler, Hermann; Willms, Lothar
Abstract : Herbicide discovery has faced significant challenges over the past few decades, and weed control innovations are urgently required . Abstract: In response to changing market dynamics, the discovery of new herbicides has declined significantly over the past few decades and has only seen a modest upsurge in recent years. Nevertheless, the few introductions have proven to be interesting and have brought useful innovation to the market. In addition, herbicide-tolerant or herbicide-resistant crop technologies have allowed the use of existing nonselective herbicides to be extended into crops. An increasing and now major challenge is being posed by the inexorable increase in biotypes of weeds that are resistant to herbicides. This problem is now at a level that threatens future agricultural productivity and needs to be better understood. If herbicides are to remain sustainable, then it is a must that we adopt diversity in crop rotation and herbicide use as well as increase the use of nonchemical measures to control weeds. Nevertheless, despite the difficulties posed by resistant weeds and increased regulatory hurdles, new screening tools promise to provide an upsurge of potential herbicide leads. Our industry urgently needs to supply agriculture with new, effective resistance-breaking herbicides along with strategies to sustain their utility.